Azines from one-pot reaction of thiosemicarbazones. (2nd January 2017) - Aly, Ashraf A.; Hassan, Alaa A.; Brown, Alan B.; Ibrahim, Mahmoud A. A.; AbdAl-Latif, El-Shimaa S. M.
ABSTRACT: Thermolysis and/or microwave irradiation of thiosemicarbazones gave the corresponding isothiocyanates, which on addition of either activated nitriles or aldehydes furnished various types of azines. The mechanism was discussed. The structures of products were proved by MS, IR, NMR, and elemental analyses. GRAPHICAL ABSTRACT: